3D 14N/1H Double Quantum/1H Single Quantum Correlation Solid‐State NMR for Probing the Parallel and Anti‐Parallel Beta‐Sheet Arrangement of Oligo‐Peptides at Natural Abundance. Issue 15 (8th June 2018) - Hong, You‐lee; Asakura, Tetsuo; Nishiyama, Yusuke
Abstract: The beta (β)‐sheet structures of oligopeptides and polypeptides can be formed in anti‐parallel (AP) and parallel (P) forms, which is an important feature to understand such structures. In principle, P‐ and AP‐β‐sheet structures can be identified by the presence (AP) or absence (P) of inter‐strand 1 HNH / 1 HNH correlations on a diagonal in the corresponding 2D 1 H double quantum (DQ)/ 1 H single quantum (SQ) spectrum due to the different inter‐strand 1 HNH / 1 HNH distances between the two arrangements. However, the 1 HNH / 1 HNH peaks overlap with the 1 HNH3 + / 1 HNH3 + peaks, which always give cross‐peaks regardless of the β‐sheet arrangement. The 1 HNH3 + / 1 HNH3 + peaks disturb the observation of the presence/absence of 1 HNH / 1 HNH correlations and the assignment of 1 HNH and 1 HNH3 + is not always available. Here, 3D 14 N/ 1 H DQ/ 1 H SQ correlation solid‐state NMR experiments at fast magic angle spinning (70 kHz) are introduced to distinguish AP‐ and P‐β‐sheet structures. The 14 N dimension allows the distinction of 1 HNH / 1 HNH peaks from 1 HNH3 + / 1 HNH3 + peaks with clear assignments of 1 HNH and 1 HNH3 + . In addition, the high natural abundance of 1 H and 14 N enables 3D 14 N/ 1 H DQ/ 1 H SQ experiments of oligo‐alanines (Ala3‐6 ) in four hours without isotope labelling. Abstract : A method to identify the β‐sheet alignment is presented based on 1 H/ 1 H homonuclear correlations with 14 N filtering. While the NH‐NH correlation does not appear in the parallel β‐sheet alignment, the presence of NH‐NH correlation identifies the anti‐parallel alignment.